Greensporone C, a Freshwater Fungal Secondary Metabolite Induces Mitochondrial-Mediated Apoptotic Cell Death in Leukemic Cell Lines - Prabhu, Kirti S.; Siveen, Kodappully Sivaraman; Kuttikrishnan, Shilpa; Iskandarani, Ahmad N.; Khan, Abdul Q.; Merhi, Maysaloun; Omri, Halima E.; Dermime, Said; El-Elimat, Tamam; Oberlies, Nicholas H.; Alali, Feras Q.; Uddin, Shahab (Frontiers in Pharmacology, 2018)
Therapeutic agents used in the treatment of cancer are known to develop resistance against cancer cells. Hence, there is a continuing need to investigate novel agents for the treatment and management of cancer. Antitumor activity of greensporone C (GC), a new resorcylic acid lactone isolated from an organic extract of a culture of a Halenospora sp. freshwater fungus, was subjected for screening against a panel of leukemic cell lines (K562, U937, and AR320). In all the three cell lines, cell proliferation was inhibited in dose dependent fashion. GC further arrested the cells in SubG0 phase in dose dependent manner. Annexin V/PI dual staining data confirmed apoptotic death of treated K562 and U937 leukemic cells. Treatment with GC suppressed constitutively phosphorylated AKT and downregulated expression of inhibitor of apoptotic proteins XIAP, cIAP-1, and cIAP-2. In summation to this, GC treated leukemic cells upregulated protein expression of pro-apoptotic proteins, Bax with concomitant decrease in expression of anti-apoptotic proteins including Bcl-2, and Bcl-xL. Upregulation of Bax was associated with cytochrome c release which was confirmed from the collapse of mitochondrial membrane. Released cytochrome c further activated caspase cascade which in turn initiated apoptosis process. Anticancer activity of this isolated fungal compound GC was potentiated via stimulating production of reactive oxygen species (ROS) along with depletion of reduced glutathione (GSH) levels in K562 and U937 leukemic cells. Pretreatment of these cells with N-acetyl cysteine (NAC) prevented GC-induced depletion of reduced glutathione level and mitochondrial-caspase-induced apoptosis. Altogether, our data show that greensporone C modulates the apoptotic response of human leukemic cells and raises the possibility of its use as a novel therapeutic strategy for hematological malignancies.